Evidence‐based medicine: What has happened in the past 50 years?. (24th December 2014) - Mellis, Craig
Abstract Although the phrase 'evidence‐based medicine' (EBM) was used for the first time in the medical literature less than 25 years ago, the history of EBM goes back for centuries. What is remarkable is how popular and how globally accepted the EBM movement has become in such a short time. Many famous, past clinicians have played major roles in the disciplines that preceded EBM, particularly 'clinical epidemiology'. It soon became clear to the early EBM champions that 'evidence' was only part of the clinical decision‐making process. Consequently, both clinical expertise and the patient's values and preferences were rapidly incorporated into the concept we now know as 'EBM'. The current need for high‐quality, easily accessible 'evidence‐based summaries' for busy clinicians is now apparent, as traditional EBM requires both considerable time and skill. Consequently, there is a progressive move away from the primary literature (such as randomised controlled trials) to systematic reviews and other 'evidence‐based summaries'. The future of EBM will almost certainly involve widespread utilisation of 'clinical (computer)‐based decision support systems'.